2016
DOI: 10.1140/epjst/e2015-50267-7
|View full text |Cite
|
Sign up to set email alerts
|

Patchy colloidosomes – an emerging class of structures

Abstract: Abstract.A colloidosome, i.e., a selectively permeable capsule composed of colloidal particles forming a stable homogenous shell, is a tiny container that can be used for storage, transportation, and release of cargo species. There are many routes to preparing colloidosomes; dozens of examples of future applications of such colloidal capsules have been demonstrated. Their functionality can be further extended if the capsules are designed to have heterogeneous shells, i.e., one or more regions (patches) of a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…207 For more colloidal capsules with a patchy surface structure we recommend the recent review by Rozynek and Jozefczak. 208 Besides these MOF-based and bimodal structures, a variety of capsules with oblong building blocks have been reported. Noble and co-workers first reported the use of microrods for the stabilization of a Pickering-like emulsion and subsequent capsule formation.…”
Section: Building Blocks and Colloidal Capsules With Distinct Morpholmentioning
confidence: 99%
“…207 For more colloidal capsules with a patchy surface structure we recommend the recent review by Rozynek and Jozefczak. 208 Besides these MOF-based and bimodal structures, a variety of capsules with oblong building blocks have been reported. Noble and co-workers first reported the use of microrods for the stabilization of a Pickering-like emulsion and subsequent capsule formation.…”
Section: Building Blocks and Colloidal Capsules With Distinct Morpholmentioning
confidence: 99%
“…8 Moreover, such drops possess characteristics that make them useful as experimental model systems for studying, for example, particle effects on interfacial tension, 9 particle crystal growth and ordering or particle layer buckling on curved interfaces, [10][11][12][13] particle assembly and rearrangement on drop surfaces, 14,15 and particle detachment from drops. 16 Particle-covered drops can additionally be employed for fabricating porous structures, 17 granular or colloidal capsules of different mechanical properties, morphologies, or shapes, 18,19 and adaptive structures. 20 In this context, broadening knowledge of particle-covered drop stability, deformation, and surface particle manipulation is essential to further developing the abovementioned research areas.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this techniques, Nudurupati et al demonstrated that it was able to extract particles inside the droplet [ 170 ] ( Figure 11 C). Rozynek et al suggested that the release rate of some areas of the droplet, named releasing holes, can be increased by rearranging the particles using an electric field [ 171 ] ( Figure 11 D).…”
Section: Applicationsmentioning
confidence: 99%
“…( C ) Removal or collection of particles from a w/o emulsion using an electric field [ 170 ]. ( D ) The releasing holes for material transportation from/to the capsule [ 171 ].…”
Section: Figurementioning
confidence: 99%